Unidades geoambientais da Bacia hidrográfica do rio das Antas, Paraná: potencialidades e fragilidades - Periçato, André Jesus (2018)
The objective of the research is the definition of geoenvironmental units in the Antas Watershed, in Cruzeiro do Oeste in the State of Paraná, highlighting potentialities and environmental fragility. To this purpose, the specific objectives were based on the integrated analysis of the physical and social elements present in the study area, with the purpose of identifying homogeneous units in the watershed, as well as the diagnosis of environmental fragility in the identified sectors. The procedures were based on integrated analysis between natural and human and/or social elements. A methodology of potential fragility and emerging fragility had also been applied. In this way, it was realized the identification, in field and in the study, of various elements that compose the landscape such as hydrography, soils, precipitation, temperature, relief and the forms of use and occupation. The integrated analysis of these elements allowed the identification of different units in the Antas watershed. The study of the potential and emergent fragility, allowed to obtain a better diagnosis of the study area. As a result, the Rio das Antas watershed was subdivided into three geoenvironmental units: unit I, unit II subdivided into IIa, IIb, IIc and unit III. Unit I comprised the sector with greater dissection, as well as sector IIc. The sectors IIa and IIb were differentiated by the forms of use and occupation and by the slight difference between the slope values. Finally, sector III has as main characteristic the flat relief and the predominance of the use of pastures. The study of the fragility, allowed to recognize the existing differences and to diagnose the main fragilities and potentialities of the watershed Antas river, allowing the knowledge of the relations between the natural environment and the forms of appropriation of the man